Finger Patterns in Violin Initial Learning: The Otakar Ševčík’s Semitones System (Per Musi, 2018)
This article presents discussions about Otakar Ševčík's teaching procedures, a Czech violinist who broke with diatonic scales teaching tradition for violin initial learning with a totally different view, by publishing the Violin Method for Beginners op.6 in the late nineteenth century. Ševčík proposed the ‘Semitones System’ as a base of his teaching methodology instead of diatonic scales. Different qualitative results indicate the need and importance of in-depth studies regarding his pedagogical proposal for initial learning.